A new NCL-targeting aptamer-drug conjugate as a promising therapy against esophageal cancer - Xue Zheng; Ying Wang; Huaiyu Duan; Junqi Hou; Shiming He (Journal of Nanobiotechnology)
Abstract Esophageal cancer (EC) is one of the most common highly malignant tumors of the digestive system, with a poor prognosis under current treatment regimens. Nucleolin (NCL) is overexpressed in many tumors, and drugs specifically targeting NCL may offer a promising strategy for treating esophageal cancer. Here, we designed and prepared a novel aptamer-conjugated drug targeting NCL by AS1411 aptamer-human serum albumin (HSA)-the apoprotein of lidamycin (LDP)-active enediyne chromophore (AE), in order to achieve targeted treatment of esophageal cancer. The experimental results revealed that AS1411-HSA-LDP effectively binds to esophageal cancer cells and could be efficiently internalized by esophageal cancer cells. In the KYSE520 xenograft tumor nude mouse model, AS1411-HSA-LDP could be targeted and enriched in the tumor location for a long time. AS1411-HSA-LDP-AE exhibited a strong cell-killing activity in esophageal cancer cells, inhibited cell migration and invasion, and induced cell apoptosis. The animal studies confirmed that AS1411-HSA-LDP-AE exhibited a strong anti-tumor effect. These findings suggested that the novel NCL-targeting aptamer-drug conjugate constructed based on lidamycin exhibited a strong anti-tumor effect, providing a promising strategy for the targeted treatment of esophageal cancer.